Bargaining power in apartment sales in Corsica: A latent class approach. (October 2020) - Caudill, Steven; Detotto, Claudio; Prunetti, Dominique
This paper extends the bargaining model of Harding et al. (Harding J, Rosenthal S and Sirmans CF (2003) Estimating bargaining power in the market for existing homes, Review of Economics and Statistics 85: 178–188), to a latent class framework. This allows for differences in market power in thin and segmented markets. We estimate a latent class model using data on apartment sales in Corsica over the period 2006 to 2016. Our results indicate that the Corsican housing market has two distinct segments or regimes and that bargaining power of buyers and sellers is not the same in these two segments. In particular, we find that local French residents have strong bargaining power in Regime 1 but non-French residents have weak bargaining power. Regime 2 is characterised by strong bargaining power for local French, Corsican French and non-French participants. Based on auxiliary regressions and a comparison of weighted means associated with each regime, we conclude that compared with Regime 2, the apartments associated with the first regime are more spacious, less likely to be new, more likely to have a garden and typically have longer travel times to local amenities such as doctors, pharmacies and the downtown area. From this we conclude that apartments associated with Regime 1 are more likely to be rural and at a greater distance from the coast. Distance from a city is likely to present an informational disadvantage to non-French residents, who may already face language and legal obstacles.